RANCANG BANGUN ALAT UJI PRESTASI MOTOR 3 FASA DENGAN MENGGUNAKAN INVERTER VFD JENIS XYS-AT1 (MODEL AT1-1500X) DAN PEMBEBANAN TAMBAHAN DENGAN SISTEM REM HIDROLIK - Dudi Suparyogi,; Ade Buhori, (Journal of Innovation Research and Knowledge, 2024)
The 3-phase motor performance test equipment with rotation adjustment using the inverter model AT1-1500X and additional loading with a hydraulic brake system is designed in such a way as to obtain representative experimental data so that it can be used as a reference to implementations in real life because this tool can optimize the use of power so that the electricity used will be less than not using the tool, or in other words the efficiency of using electric power while slowing down the damage to the tool used, whether it is a motor as a driver or a tools that is drive like a motor or a load other tools used can be easily adjusted the rotational speed and torque as needed by simply changing the frequency value (Hz) via a potentiometer switch installed on the panel, the operating pattern mentioned above is the main factor in the process of creating efficient use of electric power and inverters with single phase input and 3-phase output can be used at home where the inverter can operate a 1-phase motor by simply connecting the "W" terminal as phase and "U" as neutral so that home appliances can be regulated using electric power to make it more economical and cheap to finance